سلوك الفسفور المضاف لنماذج مختلفة من الترب في محافظة دير الزور- سوريا - السلامة ياسر (Latakia University Journal -Biological Sciences Series, 2019)
The purpose of this search was to determine the quantity of phosphate adsorbed in different soil types (calcareous, gypsum, sandy and alluvial) and to study the fitting of Langmuir isotherms equation to describe the P-adsorption process. The Langmiur equation was non-fitting to describe the P-adsorbed on tested soils when the added-P was more than 80 mg P/L, due to the interference between the adsorption process and precipitation reaction. The statistical correlation coefficients (R) between the amount of P-adsorbed and P-concentrations in solution after equilibration were significant and ranged from 0.927 (for calcareous soil) to 0.973 ( for sandy soil).Calculated Phosphorus adsorption maximum varied widely, ranging from 23.15 mg/Kg soil (for sandy soil) up to 56.50mg/Kg soil (for calcareous soil) mg P/kg soil. يهدف هذا البحث إلى تحديد كمية الفسفور المدمصة في نماذج مختلفة من الترب (رسوبية، جبسية ، كلسية ورملية ) في محافظة دير الزور، و معرفة مدى ملائمة معادلة Langmuir لعملية ادمصاص الفسفور في هذه الأراضي، ويهدف أيضاً إلى تقدير الكمية المدمصة العظمى من الفسفور في هذه الأراضي . بينت النتائج عدم ملائمة معادلة Langmuirلوصف عملية ادمصاص الفسفور في الأراضي المدروسة عندما زاد تركيز الفسفور المضاف عن 80 ملغ/ل وذلك عائداً لعملية التداخل مابين عملية الادمصاص وتفاعلات الترسيب. كما أظهرت النتائج بأن قيم معامل الارتباط للعلاقة مابين كمية الفسفور المدمصة والتركيز بعد الاتزان كانت معنوية وتراوح مابين 0.927 للتربة الكلسية و0.973 للتربة الرملية.وأن كمية الفسفور المدمصة العظمى والمحسوبة من معادلة Langmuir قد اختلفت كثيراً من 23.15 ملغ/كغ(في التربة الرملية) إلى 56.50 ملغ /كغ (في التربة الكلسية(وبالمقابل فقد أظهرت النتائج وجود علاقة موجبة مابين ثوابت معادلة Langmuir والنسبة المئوية لكربونات الكالسيوم ولم تكن هناك علاقة واضحة لباقي خواص التربة